AKTIVITAS INHIBISI Î±-AMILASE DAN Î±-GLUKOSIDASE OLEH EKSTRAK POLISAKARIDA DAN SENYAWA POLIFENOL DARI Eucheuma denticulatum DAN Sargassum hystrix - , AGUNG GIRI SAMUDRA; , Prof. Dr. Agung Endro Nugroho, M.Si, Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Alginate and polyphenol extract of Sargassum histrix and carrageenan and polyphenols extract of Eucheuma denticulatum were tested for their ability to inhibit carbohydrate hydrolysis enzymes (Î±-amylase and Î±-glucosidase) by in vitro methods. Extraction of alginate from Eucheuma denticulatum was using 0.5% KOH solution. Sodium alginate was extracted from Sargassum histrix by using 4% Na2CO3 solution. Polyphenols were extracted from both marine algae by using 50% (v/v). Identification of carrageenan and alginate was determined by Fourier Transform Infrared (FTIR) spectroscopy. Infrared spectra of polysaccharide standards (Îº- carrageenan standard and sodium alginate standard) were obtained as comparison. Total polyphenols contents from the extracts were determined according to the Folin-Ciocalteu method. Carrageenan and polyphenols extracts from Eucheuma denticulatum showed the ability to inhibit the activity of Î±-amylase with an IC50 12.16 and 11.64 mg / mL and no inhibit the activity of Î±-glucosidase with an IC50. Alginate and polyphenols extracts from Sargassum hystrix showed the ability to inhibit the activity of Î±-amylase with an IC50 15.75 and 11.26 mg / mL and polyphenols inhibit the activity of Î±- glucosidase with an IC50 9.57 mg / mL. Polyphenols extract from Sargassum hystrix were more effective to inhibit Î±-amylase and Î±-glucosidase than extract alginate from Sargassum hystrix, and carrageenan and polyphenols extract from Eucheuma denticulatum.